Impact of COVID-19 on Consumer Behaviour in Regards to FMCG - Iyengar, Srirang; Biba, Danish; Aher, Sasha (International Journal of Recent Advances in Multidisciplinary Topics, 2022)
The pandemic, COVID-19 has resulted in a massive change in the operations of the FMCG industry in India and the way it has been functioning over the years has also changed. this research paper shows how relevant this statement is and how secondary and primary research has proven it right or wrong. By the use of primary research there is answers from a ground level and with edition of secondary research there it’s a backing to the findings of the primary research.